2008
DOI: 10.1128/jb.00310-08
|View full text |Cite
|
Sign up to set email alerts
|

Population Heterogeneity inCorynebacterium glutamicumATCC 13032 Caused by Prophage CGP3

Abstract: The genome of Corynebacterium glutamicum type strain ATCC 13032 (accession number BX927147) contains three prophages, CGP1, CGP2, and CGP3. We recently observed that many genes within the CGP3 prophage region have increased mRNA levels in a dtxR deletion mutant that lacks the master regulator of iron homeostasis (J. Wennerhold and M. Bott, J. Bacteriol. 188:2907-2918, 2006). Here, we provide evidence that this effect is due to the increased induction of the prophage CGP3 in the dtxR mutant, possibly triggered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 32 publications
(46 reference statements)
2
61
0
Order By: Relevance
“…In recent studies we observed a spontaneous excision of the prophage CGP3 in a small number of C. glutamicum cells cultivated in shake flasks with CGXII minimal medium (5). Transcriptome analysis revealed an upregulation of CGP3 genes (cg1890 to cg2071) upon induction of the SOS response by addition of the DNA-cross-linking antibiotic mitomycin C (A. Heyer and J. Frunzke, personal communication).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent studies we observed a spontaneous excision of the prophage CGP3 in a small number of C. glutamicum cells cultivated in shake flasks with CGXII minimal medium (5). Transcriptome analysis revealed an upregulation of CGP3 genes (cg1890 to cg2071) upon induction of the SOS response by addition of the DNA-cross-linking antibiotic mitomycin C (A. Heyer and J. Frunzke, personal communication).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that the large prophage CGP3 (187 kb) retains the ability to be excised from the genome and exist as a circular DNA molecule. Interestingly, a small number of wild-type cells showed a much higher copy number of circular phage DNA per cell than the average of the population (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate the applicability of the PBLR for fluorescence based time-lapse studies, we investigated the fluorescence emission of a C. glutamicum strain producing a plasmid-encoded YFP-TetR fusion protein under control of the Ptac promoter (pEKEx2-yfp-tetR) 18,22 . In the presence of low inducer (IPTG) concentrations, expression from Ptac is known to lead to significant cell-to-cell variation in isogenic bacterial populations.…”
Section: Fluorescence Analysismentioning
confidence: 99%
“…In ATCC 13032, CGP1 and CGP2 are rather small (13.5 kbp and 3.9 kbp, respectively) and appear to be highly degenerated. CGP3 (187.3 kbp) is one of the largest known prophages, constituting almost 6% of the entire C. glutamicum genome, and previous studies revealed spontaneous induction of CGP3 in a small fraction of wild-type cells even under standard cultivation conditions (23). A mutant lacking the master regulator of iron homeostasis (C. glutamicum ⌬dtxR) also exhibited increased CGP3 gene expression (24).…”
mentioning
confidence: 99%